(untitled) (El Taco en la Brea, 2025)
n the centenary of surrealism, wondering about its survival, it is worth looking at Le jeu de Marseille (1941), a surrealist tarot in which a clear path for the rebellious imagination is projected. The project resonates with Breton’s exhortation to guide surrealism towards a «deep concealment», which prevents its appropriation by the public, the new social subjectivity generated by the media, convergent with contemporary fascisms. This deck, a surreal synthesis of the French deck with the Marseille tarot, offers, like the manifestos, a coordinate system for the recreational use of the collective. Each arcane encrypts a library that Nazism consigns to the fire. With its multiple combinations, the deck is presented as a route to the unexplored «logical zones» of modernity. The cards are also the access route of the Latin American imagination to the Tarot of Marseille. Latin America resonates in the cards of the Montevideo native Lautréamont and that of Alicia, by Wifredo Lam, as well as in the arcane Pancho Villa, by Max Ernst. Through this Mexican route, Alejandro Jodorowsky projects a surreal experience in the cult cinema of the 70s and, years later, embarks on the of the Tarot of Marseille.